2004
DOI: 10.1111/j.1740-0929.2004.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of sheep offered ammonia, or urea‐calcium hydroxide treated rice straw as an only feed

Abstract: The effect of ammonia (AS) and urea‐calcium hydroxide (US) treated rice straw as a sole diet on the voluntary intake, digestibility of feed components, nitrogen retention, rumen parameters and microbial nitrogen yield of Suffolk ewes, were compared in a double 2 × 2 latin square design. The digestibility of feed components was not differed in sheep offered either AS or US. Dry matter intake was higher in AS (28 g/kg BW0.75) than US (22 g/kg BW0.75). Although there was high nitrogen intake in sheep given AS die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Positive NB was also reported in sheep fed ammonia treated rice straw (Elseed, 2004) and urea treated wheat straw retaining 1.67 g N per day (Sahoo et al, 2002). Similar to the present findings, Yankasa bucks supplemented with ficus foliage as a protein source on urea treated maize stover has improved (117.7% over unsupplemented) protein retention (Abdu et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Positive NB was also reported in sheep fed ammonia treated rice straw (Elseed, 2004) and urea treated wheat straw retaining 1.67 g N per day (Sahoo et al, 2002). Similar to the present findings, Yankasa bucks supplemented with ficus foliage as a protein source on urea treated maize stover has improved (117.7% over unsupplemented) protein retention (Abdu et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, Fadel Elseed () suggested that the feed value of low‐quality roughage can be improved by alkali treatment. For example, sodium hydroxide has been shown to be effective for cleaving esterified bonds within the plant cell wall architecture and improving the ruminal digestion of cereal straw (Sundstol ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the previous studies have shown that the feed value of low‐quality roughage can be improved in the presence of ammonia, while safe and convenient methods to further improve feed value are needed (Pradhan et al. 1996a,b; Fadel Elseed 2004). Urea treatment is considered a safe method with a similar effect of improving the forage value of low‐quality roughage (Nishino 2004).…”
Section: Introductionmentioning
confidence: 99%